2007
DOI: 10.1111/j.1365-3083.2007.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LT‐K63 and CpG2006 on Phenotype and Function of Murine Neonatal Lymphoid Cells

Abstract: The immature state of the immune system of neonates makes them vulnerable to infectious agents, including Streptococcus pneumoniae. The aim of our study was to analyse and compare the effects of Escherichia coli heat‐labile enterototoxin (LT)‐K63 and CpG2006 on cells and key molecules of the neonatal immune system, using a previously established immunization model with pneumococcal polysaccharide of serotype 1 conjugated to tetanus toxoid (TT) (Pnc1‐TT). The cellular response was evaluated by measuring cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
1
13
2
4
Order By: Relevance
“…We have previously shown that the TLR9 agonist, CpG2006, enhances Pnc1-TT-induced antibody responses in neonatal mice, and activates B cells and dendritic cells [32,33]. IC31 Ò signals through TLR9 [20] similar to CpG-ODN, but one dose of Pnc1-TT with HD or LD IC31 Ò elicited higher Ab response than when given with CpG2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the TLR9 agonist, CpG2006, enhances Pnc1-TT-induced antibody responses in neonatal mice, and activates B cells and dendritic cells [32,33]. IC31 Ò signals through TLR9 [20] similar to CpG-ODN, but one dose of Pnc1-TT with HD or LD IC31 Ò elicited higher Ab response than when given with CpG2006.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the IgG subclass pattern of mice receiving IC31 Ò , revealed strong IgG1 and IgG3 responses with much lower IgG2a and IgG2b responses that nevertheless were slightly higher in the groups receiving IC31 Ò than those receiving no adjuvant. The effects of IC31 Ò on the cellular responses in neonates remain to be studied in order to directly demonstrate if IC31 Ò can overcome the Th2 bias of the neonatal immune system as we have previously shown for LT-K63 [32].…”
Section: Discussionmentioning
confidence: 99%
“…Three weeks after neonatal priming with Pnc1-TT with or without LT-K63, 10 7 spleen cells/ml in complete RPMI 1640 were incubated with or without TT (10 mg/ml) in 24-well plates (Nunc) at 37˚C, 5% CO 2 for 48 h (20). Supernatants (kept at 270˚C) were incubated for 2 h in plates (MaxiSorp; Nunc), coated with anti-mouse TNF-a (R&D Systems), and blocked with PBS 1% BSA (Sigma).…”
Section: Tnf-a Levels In Supernatant Of Spleen Cells Stimulated With mentioning
confidence: 99%
“…MultiScreen High protein binding immobilon-P membrane plates (Millipore Corporation, Bedford, MA) were coated with 20 mg/ml PPS-1 or 10 mg/ml TT overnight at 37˚C, blocked with complete RPMI 1640, serial dilutions of spleen cell (10 8 cells/ml) in complete RPMI 1640 (Life Technologies BRL, Life Technologies, Paisley, U.K.) (20) were incubated for 5 h at 37˚C, washed and incubated with ALP-goat anti-mouse IgG (Southern Biotechnology Associates) overnight at 4˚C, and developed by 5-bromo-4-chloro-3-indolylphosphate and NBT in AP development buffer (Bio-Rad Labs, Hercules, CA). Spots were counted using a microscope (Zeiss, Oberkochen, Germany) and analyzed with KS ELISPOT (Zeiss).…”
Section: Enumeration Of Abscs By Elispotmentioning
confidence: 99%
See 1 more Smart Citation